Atypical presentations of hepatitis A infection in children - Sayma Rahman Munmun; Archana Shrestha Yadav; Mohammad Benzamin; Abu Sayed Mohammad Bazlul Karim; Mohammad Rukunuzzaman; Mohammad Wahiduzzaman Mazumder; Suborna Rani Das (Indonesian Pediatric Society, 2021)
Background Hepatitis A is the most common cause of acute viral hepatitis, with a typical simple, self-limiting course. But it is not free from complications. Atypical presentations, such as in the form of prolonged cholestasis, ascites, pleural effusion, relapsing hepatitis, or fulminant hepatic failure, pose challenges to disease management. Knowledge about varying presentations and identification of factors associated with atypical presentations will help to early diagnosis of atypical courses of disease. Objective To describe various atypical clinical presentations, biochemical findings of hepatitis A infection, and possible related factors. Methods Ninety-five children aged 1 to 18 years, diagnosed with hepatitis A infection, and admitted to the Department of Pediatric Gastroenterology & Nutrition, BSMMU, Dhaka, Bangladesh from January 2015 to May 2018 were studied retrospectively. Results Atypical presentations were manifested in 19 (20%) out of 95 children with hepatitis A virus (HAV) infection. The mean age of atypical patients [6.32 (SD 3.45) years] was significantly lower than that of typical patients [8.22 (SD 3.58) years] (P=0.0041). The most common atypical manifestation was ascites (11/19), followed by hepatic encephalopathy (9/19), acute liver failure (719), thrombocytopenia (2/19), pleural effusion (2/19), and cholestasis (1; 1.1%). Children with atypical features had significantly higher international normalized ratio (INR) and serum bilirubin, as well as lower hemoglobin level than the typical group. Children of atypical group had significantly higher number of organomegaly and coagulopathy. Conclusion Ascites, hepatic encephalopathy, acute liver failure, thrombocytopenia, pleural effusion, and prolonged cholestasis were common forms of atypical presentation. Younger age, organomegaly, higher bilirubin level, prolonged PT, and decreased hemoglobin level could be predictive of an atypical presentation of HAV in children.